Fictions, nation-building and ideologies of belonging in children's literature: an analysis of Tunzi the Faithful Shadow - Tagwirei, Cuthbeth (Springer, 2016)
This article demonstrates, through Michael Gascoigne’s Tunzi the Faithful Shadow (1988), that literature for children is sometimes employed by the government into the service of propagating dominant state ideologies in Zimbabwean schools. Such texts disseminate issues of inclusion and exclusion that characterise all nation building projects. I argue, through a reading of Tunzi the Faithful Shadow, that texts for children studied in Zimbabwean schools have been shaped by a distinctly Zimbabwean socio-historical context which includes, but is not limited to, the formation of a new national sensibility after the liberation war and the political unrest in the emerging nation.